Pengaruh Karakteristik Pemerintah Daerah, Opini Audit, dan Rasio Kemandirian terhadap Pengungkapan Laporan Keuangan Pemerintah Daerah - Utami, Shafira Ramadhia; Sulardi, Sulardi (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2019)
This study aims to provide evidence of the effect of local government characteristics which consist of population, Human Development Index, audit opinion, and independence ratio on the mandatory disclosure of financial statements of local governments. The sample was local governments in Indonesia in 2017 that meets the criteria. The results of the analysis of 458 local governments in Indonesia showed the average of local governments financial statements disclosure is 60.42%. Furthermore, the results also show that the population and Human Development Index variables affect positively on the disclosure of local government financial statements. Meanwhile, the disclosure of local government financial statements is not affected by audit opinion and independence ratio. Penelitian ini bertujuan memberikan bukti pengaruh karakteristik pemda yang terdiri dari populasi, indeks pembangunan manusia (IPM), opini audit, dan rasio kemandirian pada pengungkapan wajib dalam laporan keuangan pemda. Sampel penelitian yaitu pemerintah kabupaten/ kota di Indonesia pada tahun 2017 yang memenuhi kriteria. Hasil analisis pada 458 pemda menunjukkan rerata pengungkapan pada laporan keuangan pemda sebesar 60,42%. Lebih lanjut, hasil analisis juga menunjukkan variabel populasi dan IPM berpengaruh positif pada pengungkapan laporan keuangan pemda, sedangkan variabel opini audit dan rasio kemandirian daerah tidak memengaruhi pengungkapan laporan keuangan pemda.